A Case of Subacute Bioresorbable Vascular Scaffold Thrombosis, What was Wrong? - Abualnaja, Seraj A. (Am J Case Rep, 2017)
Patient: Male, 42 Final Diagnosis: Mid to distal left anterior artery disease Symptoms: Chest pain Medication: — Clinical Procedure: Percutaneous coronary intervention Specialty: Cardiology OBJECTIVE: Unusual clinical course BACKGROUND: The introduction of bioresorbable vascular scaffolds (BVS) into the field of percutaneous coronary intervention (PCI) was thought to be a promising step in solving the issues raised with the use of early bare metal stents (BMS) and drug eluting stents (DES); however, studies have raised concerns regarding thrombosis risk associated with the use of these stents. CASE REPORT: A 42-year-old male presented with acute coronary syndrome (ACS), on diagnostic coronary angiography he had 75% and 70% stenosis in mid and distal left anterior descending artery (LAD) respectively, PCI with BVS implantation was done. A week later, he came with non-ST segment elevation myocardial infarction due to an in-stent thrombosis. Procedures to open the LAD were done with multiple balloon angioplasties and aspiration thrombectomy, following aggressive dilatation there was a class-III perforation which was sealed by covered stent. A second look angiography was done which showed patent LAD and well expanded stents. CONCLUSIONS: Since several factors play a role in decision-making regarding the selection of patient in whom BVS usage can be beneficial, larger studies are needed. Moreover, the safety profile of BVS should be investigated thoroughly.